The Iberian settlement in the Upper Guadiana Basin - García Huerta, Rosario; Morales Hervás, Javier (Complutum, 2011)
This paper presents the results of the recent research on the Iberian Iron Age sites conducted in the Upper Guadiana basin of the Ciudad Real province (Castilla-La Mancha). The research included excavations and archaeological surveys conducted in this area for two decades, setting up the foundation of a model of settlement in this territory during the development of the Iberian culture.